Tooth whitening simplifying the clinical protocol: clinical case report (Research, Society and Development, 2021)
Objective: This study aims to simplify the clinical protocol of tooth whitening. Methodology: This is a clinical case report of descriptive analytical nature (Pereira et al., 2018) Clinical case report: MSG patient, male, sought the Fametro dental clinic seeking dental treatment, where he identified through the anamnesis - there is a discomfort with darkened teeth, making it possible to diagnose the patient and present some options for tooth whitening, where he opted for in-office whitening. In the oral examination, restoration of composite resins in elements 12 and 22 was identified. Therefore, in the first session, the prophylaxis and color registration of the Vita pan scale (Classical B1 – D4) with a score of A3 was performed, as well as the use of a retractor lip and gingival barrier for soft tissue protection. The clinical mirror was also used to verify the existence of uncovered tissue and the desensitizer was applied before the whitening gel. A 35% hydrogen peroxide bleaching agent (Whitness HP Automixx / FGM) was used and, after the action, the product was removed with a suction cannula, washed with plenty of water and the gingival barrier was removed. Final considerations: Thus, the results found were satisfactory, providing a tooth whitening from A3 to B1, enabling a tooth whitening with a simple procedure and mainly with a reduced interval time from seven days to three days, providing a result in less time, but with proven effectiveness.